Neutralization of contrast in the vowel system of Urhobo - Rose O. Aziza (Studies in African Linguistics, 2008)
Urhobo, a South Western Edoid language of the Niger-Congo family, is spoken in Delta State, Nigeria. In the synchronic phonology of the language, there are seven surface vowels: [i, e, E, a, J, 0, u], but the behavior of some vowels, especially e, 0, G, is sometimes at variance with their expected vowel behavior, indicating that there may be abstract underlying vowels */r, v, ;)1 which have merged with Ie, 0, EI. The result, when compared with sister languages such as Degema and Isoko, is that the Urhobo system appears quite complex. The focus of this paper is showing that abstract underlying */r, v, ;)1, which are Proto Edoid vowels, still have an effect in the synchronic phonology: thus, Ir, el become [e], lv, 01 become [0], and I;), EI become [E] and possibly [ a]. When we account for the 'awkward' behavior of apparent Ie, 0, E/, the Urhobo vowel system is clear and straightforward.